ULTRASOUND AND COLOR DOPPLER IN THE DIAGNOSIS OF UTERINE FIBROIDS IN WOMEN WITH CHRONIC PELVIC PAIN SYNDROME - Ібадова, Ш.Т. (World of Medicine and Biology, 2017)
The article deals with the issues of ultrasound examination and color dopplerography in the diagnosis of uterine fibroids in women with chronic pelvic pain syndrome. Echography of pelvic organs in 3D and color dopplerography were performed on 84 patients with uterine myoma. When examining patients with uterine myoma, special attention was paid to determining the topography of the pelvic organs, the location of myomatous nodes and their blood supply, and also assessed the state of the uterus. It has been shown that high-resolution 3D-echography in color doppler mode can provide some help to clinicians in establishing the causes of pelvic pain syndrome in patients with uterine myoma. During the study, the following typical ultrasound signs of proliferating uterine fibrobuses were distinguished: heterogeneous tumor structure, increased echogenicity, hyperechogenic inclusions, anechogenic cavities of various sizes and forms. To evaluate peripheral hemodynamics in patients with uterine myoma and the degree of vascularization of myomatous nodes, a dopplerometric study and color Doppler mapping were used. Color Doppler mapping and dopplerometry were carried out in the right and left uterine arteries, in the radial arteries, in the peripheral arteries that feed myoma, as well as in the central, intra-tumor vessels.
Keywords: uterine myoma; pelvic pain; ultrasound; color dopplerography